Narratives of Transgender People Detained in Prison: The Role Played by the Utterances “Not” (as a Feeling of Hetero- and Auto-rejection) and “Exist” (as a Feeling of Hetero- and Auto-acceptance) for the Construction of a Discursive Self. A Suggestion of Goals and Strategies for Psychological Counseling - Hochdorn, Alexander; Faleiros, Vicente P.; Valerio, Paolo; Vitelli, Roberto (Frontiers in Psychology, 2018)
Purpose: Understanding how transgender people, who committed criminal offences and are detained in prison, produce a narrative representation of self within different prison contexts. More specifically, this study has been based on two sub-aims: On a paradigmatic level, it has been aimed at critically investigating how the discursive positioning among the Self and the Other might promote the internalization of positive and/or negative attitudes toward the self. On a pragmatic level, it intends to offer some suggestions for goals and strategies of psychological counselling with these inmates inside such highly institutionalized contexts. Method and Materials: In total, 23 in-depth interviews were conducted with transgender women detained in either female or male prison contexts in Italy and Brazil. The lexical, semantic, and semiotic structure of the transcribed interviews has been investigated by adopting the quali-quantitative software Iramuteq for performing statistical text-mining analysis. Frequency, correspondences, and distribution of the most representative utterances across the corpus of data have been accessed and critically analyzed. Results: The findings showed that transgender inmates in Brazil made repeated use of the adverb “not,” while the verb “exist” became the most representative word for the Italian sample. In Brazil, indeed, transgender women assumed masculine-driven behavior due to a common imprisonment with cis-gender men. On the contrary, transgender women in Italy are detained in protected sections, where they are allowed to wear female clothing and continue hormonal treatments. Surprisingly, transgender inmates in Italy suffered more violence in a female sector when compared to exclusively male jails. Conclusions: Transgender people represent a challenge for prison administration because it is not clear in which penitentiary context they should be detained. They should receive special attentions in order to face their special needs, which are radically different when compared to other typologies of inmates. Within penitentiary contexts, psychological counseling with transgender women should pay a special attention to the several psycho-social dimensions of this existential condition. In particular, psychological counselors should consider its inner complex articulation within different social, cultural and normative contexts.